Evaluation of lung function in a German single center cohort of young patients with sickle cell disease using EIT and standard techniques - Rein, Alina; Ngo, Chuong; van den Berg, Maike; Böll, Svenja; Lassay, Lisa; Kontny, Udo; Wagner, Norbert; Leonhardt, Steffen; Tenbrock, Klaus; Verjans, Eva (Frontiers in Medicine, 2023)
Background and objective: Sickle cell disease (SCD) is a very common autosomal recessive hemoglobinopathy leading to multiple pulmonary complications that are closely associated with mortality. The pathophysiology of chronic pulmonary involvement is not yet fully understood and no specific therapies are available. Methods: The aim of this cross-sectional study was to characterize the lung function of children and young adolescents with SCD in a German single-center cohort and to extend conventional lung function testing by the use of a new imaging method. We performed spirometry and body plethysmography in 35 children and young adults with hemoglobin SS, SC, S/β-thalassemia as well as 50 controls. These data were compared with clinical characteristics and typical laboratory parameters of hemolysis and disease activity in SCD. To identify lung inhomogeneities, for example due to atelectasis, hyperinflation, air trapping or vascular occlusions, we used the promising new method of electrical impedance tomography (EIT) and calculated global inhomogeneity indices. Results: The lung function of patients with SCD was discovered to be significantly weaker compared to that of healthy controls. When the result was found to be pathological, the most commonly observed type of breathing disorder was classified as restrictive. Laboratory parameters showed typical features of SCD including decreased levels of hemoglobin and hematocrit and elevated levels of leucocytes, platelets, lactate dehydrogenase and total bilirubin. However, there was no correlation between blood values and reduced lung function. Electrical impedance tomography (EIT) revealed no abnormalities in SCD patients compared to healthy controls. In particular, we were unable to demonstrate any regional inhomogeneities in lung ventilation. Conclusion: In our study, we found that SCD patients tend to have impaired lung function, and a significant percentage of them even have a restrictive breathing disorder, although no obstructive signs were present. Our new electrical impedance tomography (EIT) measurements revealed no unevenness that would suggest air entrapment, blockage of blood vessels, excessive inflation, obstruction, or other forms of lung disease. Additionally, the reduction in lung function observed in SCD patients was not related to the severity of their condition or laboratory test results.